Professor Oktawiusz Jurewicz as a Byzantinist (1926–2016) - Kompa, Andrzej; Leszka, Mirosław J. (Studia Ceranea, 2016)
The authors summarize the academic legacy of late Oktawiusz Jurewicz and his role as a leading Polish byzantinist of the second half of the 20th century. The text is supplemented by the detailed and updated bibliography of Jurewicz.